DOCUMENTARY PHOTOGRAPHY AS PART OF VISUAL HISTORY AND ANTHROPOLOGY - Овчаренко, Тетяна; Кобець, Катерина (SWorldJournal, 2025)
The article is devoted to the study of the role, significance and city of documentary photography in the modern conditions of the war in Ukraine. Analysis of photography as a text of culture should be carried out in the following directions – as a "creati